2011
DOI: 10.1111/j.1365-3016.2011.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of childhood obesity by infancy weight gain: an individual‐level meta‐analysis

Abstract: To assess the predictive ability of infant weight gain on subsequent obesity we performed a meta-analysis of individual-level data on 47,661 participants from 10 cohort studies from the UK, France, Finland, Sweden, the US and Seychelles. For each individual, weight SD scores at birth and age 1 year were calculated using the same external reference (British 1990). Childhood obesity was defined by International Obesity Task Force criteria. Each +1 unit increase in weight SD scores between 0 and 1 year conferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
344
2
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 367 publications
(381 citation statements)
references
References 31 publications
26
344
2
9
Order By: Relevance
“…Following studies generally found low weight gain and poor growth in infancy to be deleteriously associated with future cardio-metabolic outcomes (Eriksson et al 2003b;Forsen et al 2004). Today, rapid infant weight gain is known to be associated with obesity and obesity-related diseases (Kerkhof and Hokken-Koelega 2012; Druet et al 2012). A recent meta-analysis of approximately 50,000 individuals in high income countries found that gaining weight between birth and age 1 year greater than one centile band on a growth chart was associated with a 23 % increased odds of adulthood obesity, for example (Druet et al 2012).…”
Section: Infancymentioning
confidence: 99%
See 1 more Smart Citation
“…Following studies generally found low weight gain and poor growth in infancy to be deleteriously associated with future cardio-metabolic outcomes (Eriksson et al 2003b;Forsen et al 2004). Today, rapid infant weight gain is known to be associated with obesity and obesity-related diseases (Kerkhof and Hokken-Koelega 2012; Druet et al 2012). A recent meta-analysis of approximately 50,000 individuals in high income countries found that gaining weight between birth and age 1 year greater than one centile band on a growth chart was associated with a 23 % increased odds of adulthood obesity, for example (Druet et al 2012).…”
Section: Infancymentioning
confidence: 99%
“…Today, rapid infant weight gain is known to be associated with obesity and obesity-related diseases (Kerkhof and Hokken-Koelega 2012; Druet et al 2012). A recent meta-analysis of approximately 50,000 individuals in high income countries found that gaining weight between birth and age 1 year greater than one centile band on a growth chart was associated with a 23 % increased odds of adulthood obesity, for example (Druet et al 2012). So, how does this not contradict the findings of the earlier studies?…”
Section: Infancymentioning
confidence: 99%
“…Thus, early nutritional practices have not been backed by rigorous experimental evidence of efficacy and safety, which is expected in other areas of public health; and have the potential to cause harm. For example, 'intuitive' attempts to promote growth in small, growth-retarded newborns could significantly increase later CVD and obesity (3)(4)(5)(8)(9)(10)(11)(12)(13)(14) . This lack of a sound evidence-base has prevented changes to nutritional and public health practice in infancy in order to prevent later NCD.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…For instance, faster weight gain in infancy (upward centile crossing for weight) is associated with a greater risk of later obesity in more than thirty studies (summarised in five systematic reviews, (8)(9)(10)(11)(12) including an individual-level meta-analysis in 47 661 participants from ten cohorts (11) ). This association is seen for the main components of the metabolic syndrome, in breast-fed and formula-fed populations, in high-and low-income countries representing many different ethnic groups (7)(8)(9)(10)(11)(12) , and is consistent for cohorts during the past 80 years (8) . The association is biologically plausible and experimentally reproducible in several animal models (7) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…En effet, un faible poids à un an était, comme un faible poids à la naissance, associé au risque de décès de cause cardiovasculaire [26]. En 2002, dans un contexte nutritionnel radicalement différent, une première publication attirait l'attention sur la rapidité de la prise de poids dans les premiers mois de vie comme un facteur de risque d'obésité ultérieure [27], une observation qui a été confirmée par la suite [28]. Les six premiers mois de vie semblent représenter la période critique pour ce phénomène [29].…”
Section: Les Enjeux Liés Aux Modifications Du Statut Nutritionnel Matunclassified